Novel High Content Screen Detects Compounds That Promote Neurite Regeneration from Cochlear Spiral Ganglion Neurons - Whitlon, Donna S. (Sci Rep, 2015)
The bipolar spiral ganglion neurons (SGN) carry sound information from cochlear hair cells to the brain. After noise, antibiotic or toxic insult to the cochlea, damage to SGN and/or hair cells causes hearing impairment. Damage ranges from fiber and synapse degeneration to dysfunction and loss of cells. New interventions to regenerate peripheral nerve fibers could help reestablish transfer of auditory information from surviving or regenerated hair cells or improve results from cochlear implants, but the biochemical mechanisms to target are largely unknown. Presently, no drugs exist that are FDA approved to stimulate the regeneration of SGN nerve fibers. We designed an original phenotypic assay to screen 440 compounds of the NIH Clinical Collection directly on dissociated mouse spiral ganglia. The assay detected one compound, cerivastatin, that increased the length of regenerating neurites. The effect, mimicked by other statins at different optimal concentrations, was blocked by geranylgeraniol. These results demonstrate the utility of screening small compound libraries on mixed cultures of dissociated primary ganglia. The success of this screen narrows down a moderately sized library to a single compound which can be elevated to in-depth in vivo studies, and highlights a potential new molecular pathway for targeting of hearing loss drugs.